2013
DOI: 10.1111/opo.12069
|View full text |Cite
|
Sign up to set email alerts
|

Influence of periodic vs continuous daily bright light exposure on development of experimental myopia in the chick

Abstract: In chicks, an increase in daily light exposure continuously during the day is more effective at inhibiting myopia than adding an equivalent dose within a 2 h period of bright light. A weak time-of-day effect also appears to be present in the response to bright light exposure. Our results suggest that future light-based myopia therapies in humans may be more effective if light levels are increased over the whole day, rather than through short periods of bright light exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 48 publications
(66 reference statements)
3
27
0
Order By: Relevance
“…Short term bright light exposure for 1 or 2 hours generated only a trend towards inhibition of deprivation myopia. This result is consistent with a recent study in chickens in which bright light of 10 000 lux was provided for 2 hours a day but no significant effects were found, no matter at which time of the day it was applied [29]. In comparison, human studies show that children appear to be more “sensitive” to bright light exposure, as Jones et al observed a marked reduction in the risk of myopia when the amount of time outdoors increased from 0–5 hours per week (approximately 1 hour per day) to>14 hours per week (approximately 2 hours per day) [9].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Short term bright light exposure for 1 or 2 hours generated only a trend towards inhibition of deprivation myopia. This result is consistent with a recent study in chickens in which bright light of 10 000 lux was provided for 2 hours a day but no significant effects were found, no matter at which time of the day it was applied [29]. In comparison, human studies show that children appear to be more “sensitive” to bright light exposure, as Jones et al observed a marked reduction in the risk of myopia when the amount of time outdoors increased from 0–5 hours per week (approximately 1 hour per day) to>14 hours per week (approximately 2 hours per day) [9].…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, no relative changes in corneal radius of curvature were found by Ashby et al [13] when animals were reared under 50, 500 or 15 000 lux. Also Backhouse et al [29] did not find relative changes in chickens kept at 2,000 lux for 10 hours or at 10,000 lux for 2 hours. Interestingly, Cohen et al [12] found that corneal radius of curvature responded differently under continuous light and under normal diurnal cycles.…”
Section: Discussionmentioning
confidence: 90%
“…Consistent with the previous findings of the effects of BL across multiple species, 10,14,[42][43][44] Figure 1 shows that BL (6 hours/day) shifted refraction toward hyperopia, and inhibited FDM development by at least 46% with corresponding changes in VCD and AL. Bright light exposure for less than 2 hours/day had no effect on FDM in chicks, and was only effective when exposure times were longer than 5 hours/day, suggesting that the duration of BL exposure is an important factor in myopia control.…”
Section: D1r (At Least Partially) Mediates Bl Inhibitory Effects On Rsupporting
confidence: 90%
“…However, other potential variables, such as time of day of exposure, have not been sufficiently explored. Several recent studies hint that time of day might be important: 2 hours of bright light was more effective at myopia inhibition in form-deprived eyes when given mid-day versus evening (Backhouse et al 2013). Another study, however, showed that 5 hours of bright light was more effective in the morning than in the evening at reducing negative lens-induced myopia (Feldkaemper et al 2016).…”
Section: Discussionmentioning
confidence: 99%